ZIMBO Analisis Isi terkait Nilai Sosial dan Budaya Dalam Cerita Rakyat Di Simalungun - Nasution, Abdullah Akhyar (Department of Anthropology, 2018)
The tale of the Zimbo is one of folklore that can be found in ethnic Simalungun. Currently, in order to understanding character a group of people can also be done by reviewing content or substance of folk tales that they have. To study the value content of of social-cultural values in a folklore will be useful in identifying collective potential or characters the owners of the story. This article is written base on the document study by using content analysis method. The collection of data in this study is entirely done by studying a whole of Zimbo story. The written source of Zimbo tale retrieved from the publication of the Ministry of Education and Culture at 1996. The results of the analysis content done found that the story of Zimbo contain some social and culture values. genarally, the story of Zimbo shows that Simalungun ethnic was a religious community, keep the harmony of nature, very democratic, anti-imperialism and other socio-cultural values. Thus, dissemination of the values that exist in the content of the story of Zimbo will be very useful in the forming character Ke-Simalungunan on the young generation.